Histórias contracoloniais em Abaetetuba e Barcarena: grafias de vida e resistência do ser-em-comum na Amazônia - GUERREIRO NETO, Guilherme Imbiriba (Universidade Federal do Pará, 2023)
This thesis proposes listening and assembling counter-colonial stories told by leadership from traditional territories of Abaetetuba and Barcarena, located at Baixo Tocantins, an ancient-occupied region of the Amazon, invaded by industrial and logistical enterprises derived from the mining and agribusiness sectors. The research consists of two parts: the book Vidas em Confluência: day-to-day and struggle in Abaetetuba and Barcarena communities, with stories and life tales about the lives of eight living storytellers, mainly women of black and indigenous descent from six traditional communities; the discussion about history writing and worldview wars in the Amazon, neocolonial death tales of capital and State powers while also reassembling the life tales that make up the book. The thesis starts from the following issue: how do crossed life tales from leaderships that live on traditional communities threatened/hit by colonial-capitalist progress in Abaetetuba and Barcarena weave existence, conflicts and resistance in a way to converge, by diversity and contrast, towards shaping collective-beings in the Amazon? This question unfolds into two objectives, each one complying with each part of the thesis: (1) composing a crossed narrative using speeches and writing from the lives of community leaderships of Abaetetuba and Barcarena, that retells and reshapes stories from the collective-being in the Amazon, with its junctions and distinctions; (2) analyze the tension between life tales of the collective-being and death tales of capital and State powers in Barcarena and Abaetetuba that arise from counter-colonial thoughts and stories. The methodological path crosses worlds using cosmo-hearing, crosses languages using memory transcription and delivers a crossed composition/assembly of the stories in two ways: with a narrative quality in the book and with an analytical quality in the deduction. The hypothesis is that the methodological disruption brought up by the thesis allows to: (1) identify reproductions of the colonial event and converge to new counter-colonial entries to reshape stories from the Amazon; (2) understand thoughts and tales that surface as potential resistance to total violence and traces of existence in the midst of colonial-capitalist ruins